(untitled) (Research, Society and Development, 2022)
The objective was to analyze the temporal trend of mortality from pancreatic cancer in Brazil and its regions from 1980 to 2019. This is an ecological time series study on mortality from pancreatic cancer in Brazil and its regions in the period from 1980 to 2019. Measures of central tendency of the selected variables were calculated, as well as standardized mortality rates (SMR). The temporal trend was estimated by the JoinPoint regression model. The average Standardized Mortality Rate (SMR) in Brazil for females was 5.06 deaths per 100,000 (SD=0.91), for males the SMR was 6.49 per 100,000 (SD =0.88). In Brazil, there was a pattern of growth in the standardized mortality rate from pancreatic cancer in both sexes over the years (Average Annual Percent Change=1.0 and 1.5% male and female, respectively). The North showed non-significant AAPC indicating a stationary trend (p>0.05). The Northeast showed growth in males (AAPC=3.6%) and females (AAPC=3%). The southern region showed a decrease in males (AAPC=-9.5%) and an increase in females (AAPC=1.1%). The trend in the Southeast was of growth in males (AAPC=0.3%) and stationary in females (p>0.05). The Midwest showed an increase in both sexes (AAPC=1.8%). In the present study, it was found that males had the highest standardized mortality rate from pancreatic cancer in the entire Brazilian territory. There was a trend towards an increase in the death rate in Brazil, in the Northeast and Midwest regions.